Synthesis of amphiphilic spiropyran-based random copolymer by atom transfer radical polymerization for Co2+ recognition. (April 2015) - Cui, Huanqing; Liu, Hui; Chen, Si; Wang, Ruimeng
Abstract: An amphiphilic spiropyran-based random copolymer containing methacrylic acid unit has been prepared and investigated with obvious negative solvatochromism in five different solvents. It was found that the polarity of comonomer influenced the photochromic behavior of spiropyran. The synthesized copolymer exhibited a good reversible behavior in aqueous solution: the addition of strong acid promoted the isomerization from spiropyran (SP) to merocyanine (MC), and the inverse process was achieved by the introduction of strong base. Much more importance, the effect of comonomer was utilized for the selective Co 2+ recognition. The locations of the maximum absorption peak stay almost as same as MC when it is complexed with Cu 2+, Mn 2+ and Hg 2+ . The location, however, moves from 551 nm to 526 nm upon complexation with Co 2+ . The obvious color change of the solution from purple to claret-red after complexation with Co 2+ was observed. This interesting phenomenon is practically convenient for the visual recognition of Co 2+ . Graphical abstract: Spiropyran-based random copolymer containing MAA unit can detect Co 2+ with high selectivity and sensitivity. Highlights: Spiropyran-based random copolymer was synthesized by ATRP. The negative solvatochromism was observed. The polarity of comonomer influenced the photochromic behavior of spiropyran. MAA unit offset the protonation of MC isomer to a large extent. The random copolymer can be conveniently used to detect Co 2+ with high selectivity.